Pemberdayaan Gerakan Menjaga Lingkungan Berbasis QS. Al-A’raf: 56 dalam Perspektif Tafsir Al-Mishbah di Kelurahan Cinangka, Kota Depok: Empowering Environmental Conservation Movements Based on QS. Al-A‘raf: 56 from the Perspective of Tafsir Al-Mishbah in in Cinangka Subdistrict, Depok City - Khusna Farida; Aulia Fauziah; Mufidatun Nisa; Mutiara Zhafira (Khadimul Mujtama’: Journal of Community Service, 2025)
Environmental awareness has become an urgent need in addressing ecological challenges. Surah Al-A’raf verse 56 prohibits mankind from causing destruction on earth after Allah has set it in order, which, according to Tafsir Al-Mishbah, is interpreted as the obligation to preserve environmental balance as a divine trust. Based on these values, the Community Service in Cinangka was carried out through educative approaches such as awareness campaigns, environmental workshops, and a mass community clean-up involving residents of RW 06 and RW 07 of Kampung Kebon Cinangka. The program also emphasized the role of housewives as strategic actors in practicing wise household waste management. The results revealed increased community awareness of cleanliness, strengthened social solidarity through collective clean-up, and the establishment of a continuing initiative called the Plastic Bottle Charity Program (Sedekah Sampah), which remains active until today. These findings indicate that integrating Qur’anic values with real actions can foster sustainable ecological awareness. This program is significant as it provides an empowerment model that combines religious, social, and environmental aspects.